The effect of a non-ionic surfactant on the growth and development of tomato and wheat plants under deficit irrigation - Marais, D. (Diana) (University of Pretoria, 2022)
Dissertation (MSc (Agric): Horticultural Sciences)--University of Pretoria, 2022.